Modelling the Galaxy Bimodality: Shutdown Above a Critical Halo Mass - Cattaneo, A; Dekel, A; Devriendt, J; Guiderdoni, B; Blaizot, J (2006)
We reproduce the blue and red sequences in the observed joint distribution of colour and magnitude for galaxies at low and high redshifts using hybrid N-body/semi-analytic simulations of galaxy formation. The match of model and data is achieved by mimicking the effects of cold flows versus shock heating coupled to feedback from active galactic nuclei (AGNs), as predicted by Dekel and Birnboim (2006). After a critical epoch z=3, only haloes below a critical shock-heating mass 10^12MSun enjoy gas supply by cold flows and form stars, while cooling and star formation are shut down abruptly above this mass. The shock-heated gas is kept hot because being dilute it is vulnerable to feedback from energetic sources such as AGNs in their self-regulated mode. The shutdown explains in detail the bright-end truncation of the blue sequence at ~L*, the appearance of luminous red-and-dead galaxies on the red sequence starting already at z~2, the colour bimodality, its strong dependence on environment density and its correlations with morphology and other galaxy properties. Before z~2-3, even haloes above the shock-heating mass form stars by cold streams penetrating through the hot gas. This explains the bright star-forming galaxies at z~3-4, the early appearance of massive galaxies on the red sequence, the high cosmological star-formation rate at high redshifts and the subsequent low rate at low redshifts.